Pengaruh Frekuensi Senam Aerobik Mix Impact Selama 40 Menit Teradap Penurunan Berat Badan pada Komunitas Senam di Desa Kumendung Rembang - Lailatul Ulissyafa’ah; Rusnoto Rusnoto; Sri Siska Mardiana (Jurnal Ners, 2025)
loss in the gymnastics community in Kumendung Village, Rembang. The research design used was a quasi-experiment with a pretest-posttest design in two groups. The number of samples was 20 respondents, divided into two groups with different frequencies of gymnastics. The research instrument was in the form of a weight observation sheet, while the data analysis used a paired t-test and an independent sample t-test. The results showed that in the first group there was an average weight decrease of 2.20 kg with a value of p = 0.001, while in the second group there was an average decrease of 4.50 kg with a value of p = 0.000. This proves that 40-minute mix-impact aerobic exercise has a significant effect on weight loss, although comparisons between the two groups show no significant difference. In conclusion, mixed impact aerobic gymnastics can be used as one of the effective methods in weight loss programs, if it is done regularly and accompanied by a healthy lifestyle.